A Life from Müşirlik (Marshalship) to Exile: Mustafa Zeki Pasha (1908-1914) - Pınar Çevik Azap (Türkiyat Mecmuası)
The career of Mustafa Zeki Pasha, who was among the most important soldiers and statesmen of his period began with his graduation from Mekteb-i Harbiye. He carried himself to the ministry of Mekatib-i Umumiye-i Askerîye and Müşir (Marshal) of Tophane-i Âmire. Müşir Mustafa Zeki Pasha was dismissed from both his positions because of the events following the declaration of Constitution II. Known for his closeness to Abdulhamid II, Müşir Mustafa Zeki Pasha could not escape the wrath of public, who were members and supporters of the Union and Progress Party. After increasing reactions a few days after his dismissal, Mustafa Zeki Pasha was taken to the Ministry of War. After one month, he was released after voluntarily returning the state properties he had taken on. He was taken to Büyükada and subjected to house arrest in his mansion for a few months. After being tried at Divan-ı Harp for the March 31 incident, his military ranks were taken, and he was exiled to Rhodes. This study attempts to expose the dismissal of Müşir Mustafa Zeki Pasha, who had the opportunity to hold important positions for many years during the reign of Sultan Abdulhamid II, from his duties owing to events after the declaration of Constitution II, his arrest as a result of intensified reactions, follow-up of his detention process by the public, the process of returning government properties from his spouses and himself, and the flow of events that resulted in his exile to Rhodes, according to the testimony of the media of the period, Ottoman archive documents, and Turkish literature.